The Potential Contribution of ABO, Lewis and Secretor Histo-Blood Group Carbohydrates in Infection by Toxoplasma gondii - De Mattos, Luiz Carlos; Ferreira, Ana Iara Costa; de Oliveira, Karina Younan; Nakashima, Fabiana; Brandão, Cinara Cássia (Frontiers in Cellular and Infection Microbiology, 2021)
The glycosyltransferases encoded by genes from the human ABO, Lewis, and Secretor histo-blood group systems synthesize part of the carbohydrate antigens in hematopoietic and non-hematopoietic tissues. The combined action of these glycosyltransferases strongly influences cell, tissue, mucosa, and exocrine secretion carbohydrate phenotypes, including those serving as habitat for mutualistic and pathogenic microorganisms. A set of reports investigated associations between Toxoplasma gondii infection and the ABO histo-blood group system, but the results are contradictory. As T. gondii uses the gastrointestinal tract as a route for infection, and in this organ, the expression of ABO, Lewis, and Secretor histo-blood group carbohydrates occurs, it is reasonable to suppose some biological relationship between them. This text reviewed association studies published in recent decades focusing on the potential contribution of the ABO, Lewis, and Secretor histo-blood group carbohydrates and infection by T. gondii.